Linking Turgor with ABA Biosynthesis: Implications for Stomatal Responses to Vapor Pressure Deficit across Land Plants . Issue 3 (11th May 2016) - McAdam, Scott A.M.; Brodribb, Timothy J.
Abstract : Small reductions in leaf turgor can trigger foliar ABA biosynthesis in angiosperms, influencing stomatal responses to vapor pressure deficit. Abstract: Stomatal responses to changes in vapor pressure deficit (VPD ) constitute the predominant form of daytime gas-exchange regulation in plants. Stomatal closure in response to increased VPD is driven by the rapid up-regulation of foliar abscisic acid (ABA) biosynthesis and ABA levels in angiosperms; however, very little is known about the physiological trigger for this increase in ABA biosynthesis at increased VPD . Using a novel method of modifying leaf cell turgor by the application of external pressures, we test whether changes in turgor pressure can trigger increases in foliar ABA levels over 20 min, a period of time most relevant to the stomatal response to VPD . We found in angiosperm species that the biosynthesis of ABA was triggered by reductions in leaf turgor, and in two species tested, that a higher sensitivity of ABA synthesis to leaf turgor corresponded with a higher stomatal sensitivity to VPD . In contrast, representative species from nonflowering plant lineages did not show a rapid turgor-triggered increase in foliar ABA levels, which is consistent with previous studies demonstrating passive stomatal responses to changes in VPD in these lineages. Our method provides a new tool for characterizing the response of stomata to water availability.